2021
DOI: 10.3233/ves-201559
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the frontiers of vestibular migraine: A case series

Abstract: INTRODUCTION: Patients with episodic vestibular syndrome (EVS) whose symptoms resemble those of vestibular migraine (VM) but who do not meet the criteria for it are common. OBJECTIVE: To describe those patients suffering from EVS in whom defined etiologies have been ruled out in order to determine if their symptoms can be linked to VM. MATERIAL AND METHODS: Prospective multicenter study. The medical records of patients with VM and patients with EVS suggestive of VM but not meeting the criteria for it were exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Of the six articles without numeric age-group data, five studies found no influence of age on treatment outcome after one CRP. 24,29,37,42,61 Korres et al 51 found a better initial response to treatment in the younger age group (p < 0.001). 51…”
Section: Treatment Efficacy After One Maneuvermentioning
confidence: 94%
See 1 more Smart Citation
“…Of the six articles without numeric age-group data, five studies found no influence of age on treatment outcome after one CRP. 24,29,37,42,61 Korres et al 51 found a better initial response to treatment in the younger age group (p < 0.001). 51…”
Section: Treatment Efficacy After One Maneuvermentioning
confidence: 94%
“…Seventeen prospective studies, [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] four randomized controlled trials, [35][36][37][38] one non-randomized controlled trial, 39 two randomized trials, 40,41 and 21 retrospective studies were included. 8,26,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] An overview of the methodological quality assessment is provided in Table S1.…”
Section: Risk Of Bias In Individual Studiesmentioning
confidence: 99%
“…It is still unknown whether recurrent vestibular symptoms not otherwise specified (RVS-NOS) that do not fulfill any of the criteria of so far established entities are part of the spectrum of established disorders, or a single disease entity with distinct pathognomonic features, or a heterogeneous group of different disorders (18). Since the existing diagnostic criteria for vestibular disorders rely mainly on clinical presentation, the aim of the present study was to systematically categorize all vestibular symptoms in patients with RVS-NOS using the Bárány Vestibular Symptoms grid.…”
Section: Introductionmentioning
confidence: 99%
“…There are limited researches on the clinical differences between cVM and pVM, and some studies suggest that the patient groups’ characteristics were most pronounced for definite diagnoses ( Oh et al, 2021 ), and there are other studies that support this conclusion, suggesting that utriculo-ocular pathway dysfunction is more frequent in VM than pVM ( Fujimoto et al, 2020 ). In addition to these discussions between cVM and pVM, some studies suggest that the current criteria of VM is questionable and needs to be further refined and expanded ( Dominguez-Duran et al, 2021 ; Chae et al, 2022 ). The results of this study showed that women with cVM were approximately 3–4 times more likely than male patients, and their age matched a normal distribution, with a high prevalence in middle-aged women around 50 years of age, which is consistent with previous studies ( Dieterich and Brandt, 1999 ).…”
Section: Discussionmentioning
confidence: 99%